THE 2015 OPERATION TO EVACUATE CHINESE CITIZENS FROM YEMEN - Pawlicki Robert; Słomski Bartłomiej (2021)
The present article presents the 2015 operation for evacuation of non-military personnel from Yemen, carried out by the Armed Forces of PRC. After presenting the general characteristics of evacuation operations, we follow with the description of the Yemen operating theater, taking into account the most significant conditions that resulted in the crisis of its state structures at the end of the 20th century and at the beginning of the 21st century. The subsequent part of the article presents an overview of the Chinese presence in Yemen. Then the authors characterize the course of the evacuation, including the forces allocated to carry it out and the way the operation was actually conducted, taking into account the dates and number of people evacuated. The article is concluded with a discussion of the most significant objectives that China secured in the result of its successful NEO operation.